PENGARUH IPK, STATUS SOSIAL EKONOMI, TEMAN SEBAYA, DAN INFORMASI BEASISWA S2 TERHADAP MINAT STUDI S2 - Winda Marlyana; Tedi Rusman; Albet Maydiantoro (FKIP Universitas Lampung, 2019)
The purpose of this study was to determine the effect of GPA, socio-economic status, peers, and information on S2 scholarships on the interest in S2 studies in alumni of the Faculty of Social Sciences, FKIP Unila. The method used in this research is descriptive verification with an ex post facto approach and a survey. The population in this study amounted to 315 people. The sample obtained was 76 people, and the sampling technique was non-probability sampling with purposive sampling. Based on the analysis results, it can be concluded that there is an individual influence between GPA, social, economic status, peers, and information on S2 scholarships on interest in S2 studies in alumni of the Faculty of Social Sciences FKIP Unila class of 2015. Meanwhile, simultaneously there is an influence between CPI, socioeconomic status. , peers, and information on S2 scholarships about postgraduate study interest in alumni of the Department of Social Sciences, FKIP Unila class of 2015. The count value is 39.333 with sig. From 0,000.